Optimization study of chlorine detection sensitivity in concrete based on prompt gamma analysis using 252Cf neutron source. (October 2022) - Yan, Mingfei; Wakabayashi, Yasuo; Takamura, Masato; Ikeda, Yujiro; Otake, Yoshie
Abstract: Chloride attack is a serious problem that decreases the durability of concrete structures of bridges and highways. A compact neutron salt meter with a 252 Cf neutron source and germanium (Ge) gamma-ray detector based on prompt gamma-ray neutron activation analysis (PGNAA) has been proposed to determine the chlorine concentration in concrete structures. The Optimization of the dimensions of its components, such as polyethylene (PE) moderator, graphite reflector, and lead shield, as well as the positions of the 252 Cf source and the Ge detector has been performed to make it highly sensitive for the detection of gamma-rays of chlorine, in addition to lightweight and small volume for in situ use. The results demonstrated that gain factors of 2.5 and 2.2 were obtained for gamma-ray intensity of chlorine and chlorine-to-hydrogen ratio (CHR), respectively, whereas the weight and volume became 19.1% and 23.4%, respectively, compared with the reference setup. The effectiveness of optimization was confirmed by preliminary experiments. Highlights: A portable device to measure chlorine concentration in concrete based on PGNAA with 252 Cf neutron source was proposed. Optimization was performed by Geant4 code to make it highly sensitive and lightweight. 10 times gain with respect to detection sensitivity per weight was achieved through the optimization. Effectiveness of the optimization was validated by experiments.